Project Based Practicum Student Worksheet on Buffer Solution Material - Klaudius Ware; Klaudia E.N. Bambut; Sri Sulystyaningsih N.D. Tiring; Maria Yuvita Yovi Sirila (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2023)
Practicum-based worksheets have been proven to improve students' thinking abilities. This research aims to describe the design and determine the feasibility of a project-based practical worksheet on buffer solution material. This research uses the Borg & Gall development model which consist of analyzing potential problems stage, data collection, product design, product marketing, product analysis and revision. The research subjects were 11th grade students from two different senior high school. The validation results show that the project learning-based student worksheet is classified as very valid with a score of 93 for small scale, 96 for medium scale, and 99 for large scale. The media was declared suitable for use based on the results of trials on small, medium and large scale students in the very good category with scores of 50, 51 and 55 respectively. This shows that project-based practical worksheets on buffer solution material are suitable for application to students.